KONFORMITAS DALAM NOVEL TRILOGI DILAN KARYA PIDI BAIQ - Faradianti, Merinda; Hayati, Yenni; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This research was a qualitative research with analysis method using sociology of literature. The sociology of literature used to know the format of comformity and factorâ€™s that influence comformity in Dilan novel trilogy by Pidi Baiq. The data used were word, frase, clausa, sentences, and paraghrap. Source of researce is Dilan novel trilogy by Pidi Baiq. Data collecting method were (1) read and understanding about Dilan novel trilogy by Pidi Baiq with make a highlight regarding story that has the data, and (2) data intervension. The research result shown that two of comformity format in Dilan novel trilogy by Pidi Baiq is positive comformity such (a) active in the school, (b) like reading and writing, and (c) active for exstra activity beside school. Then negative comformity such (a) smoking, (b) not attend school, (c) fighting, (d) drug and alkohol, (e) prostitution, (f) money by force, and (g) free living style. Next, factors caused comformity was (a) attitude, (b) culture, and (c) social attend.Â Keywords: Â Teen, Conformity, Indonesian Novel